A binuclear copper-substituted phosphomolybdate with reactive oxygen species catalytic ability and antimicrobial activity. Issue 3 (7th December 2018) - Ma, Xiang; Zhang, Chao; Hua, Jiai; Ma, Pengtao; Wang, Jingping; Niu, Jingyang
Abstract : A magnetic binuclear Cu-substituted Strandberg POM can produce ROS and inhibit the growth of E. coli . Abstract : A novel 1-D phosphomolybdate based on a dinuclear copper-substituted Strandberg structure was successfully designed and synthesized. It not only possesses reactive oxygen species (ROS) catalytic ability in aqueous solution, by synergizing the Cu clusters with the building blocks, but also shows good antimicrobial activity.